(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2022)
El-Kufra oasis lies in southeastern Libya, deep in the Sahara Desert, covering an area of about 3,630 km2. Rainfall is deficient, and agriculture depends mainly on irrigation from groundwater (The Nubian aquifer). Most El-Kufra farms are private, using flood water irrigation from shallow wells (18‒55 m). The Kufra Agricultural Project (state farms) comprises 100 circles, using deep wells (220‒352 m). This study aimed to assess the quality of irrigation water from the shallow and deep aquifer in El-Kufra oasis and its effect on the soil properties and crop production (alfalfa and potato). According to the FAO classification system, 97% of the examined deep wells are suitable for irrigation, only 3% were in the slight to moderate restriction category (E.C.> 0.7 dS/m). However, 78% of the shallow wells were in the severe category degree (E.C.> 3 dS/m), and 22% were in the slight to the moderate category of restriction. The water quality is reflected in the soil properties and crop production. The soils of the state farms were in the normal range for pH, E.C., and ESP% values; meanwhile, 10% of the private farms were classified as saline-non alkali soil, and 70% as saline-alkali soils. The salt accumulation in the soil’s root zone affects crop production, most obviously in the private farms as they depend on the shallow aquifer with poor water quality and use inappropriate irrigation and cultivation techniques. This study highlighted the urgent need to transfer the agricultural sector in El-Kufra district to depend on the deep aquifer and adjust the agricultural applications and cultivated crops to be more suitable for the desert environment and salty soils.